PENGARUH PERPUTARAN KAS TERHADAP PROFITABILITAS PADA PT. INDOFOOD SUKSES MAKMUR, TBK. - Windi Novianti; Arifin Nurulloh (JURISMA : Jurnal Riset Bisnis & Manajemen, 2013)
Cash Turnover is cash the ability to generate revenue so it can be seen how many times cash spin for a specified period. Profitability is the ability of companies to earn profits in relation to sales, total assets and shareholder equity. This study aims to determine cash turnover and profitability, and how much influence the velocity of cash to profitability in PT. Indofood Sukses Makmur Tbk. The method used is descriptive method with quantitative approach. The statistical test used was simple linear regression, Pearson correlation coefficient, determination coefficient and hypothesis test. Based on this research shows that there is a relationship between the Cash Turnover to profitability. Level of relation (correlation) both variables are very low, ie r = 0.050 with the value of a positive correlation means that if the velocity of flows increases, the profitability has also increased. vice versa, Influence the level achieved was 0.25% while the rest equal to 99.75% influenced by other factors. While through hypothesis test is done using the t test, t value obtained for 0.133 and t table value of 2.365. Based on the t value, so t count < t table, so Ho accepted and Ha rejected. So we can conclude that the effect or impact of cash turnover was very low and no significant effect on profitability at PT. Indofood Sukses Makmur Tbk..Â Keywords: Cash Turnover, Profitability